Historia zespołów filmowych z dzisiejszej perspektywy - Hendrykowski, Marek (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2013)
A History of Polish Film Units from a present-day perspective Directors were central and outstanding figures in the creation of the postwar Polish film industry from the 1940s to the late 1980s. Educating young filmmakers, the Film School in Łódź fostered a documentary-realist style of narrative filmmaking, seen in the work of such talents as Munk, Wajda, Morgenstern, Polański, Zanussi, Skolimowski, Marczewski and Kieślowski. Since 1990, the producer system has replaced the traditional structure of Polish cinema connected with the director’s pursuits and primacy, and well as film units. Marek Hendrykowski’s critical study describes this process, covering selected historical, political and cultural events. The author discusses various aspects of this evolution and the idea of the creative producer, redefining its role for generations to come.